2016
DOI: 10.1088/0952-4746/36/1/r23
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeted effects and radiation-induced carcinogenesis: a review

Abstract: Exposure to ionising radiation is clearly associated with an increased risk of developing some types of cancer. However, the contribution of non-targeted effects to cancer development after exposure to ionising radiation is far less clear. The currently used cancer risk model by the international radiation protection community states that any increase in radiation exposure proportionately increases the risk of developing cancer. However, this stochastic cancer risk model does not take into account any contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 116 publications
0
32
0
2
Order By: Relevance
“…However, an optimal RT regimen is still not clear and under current discussion [ 54 ]. Additionally, due to discussion about a possible carcinogenic late risk, the application of LD-RT is still a subject of controversial debate and less accepted in many countries [ 55 , 56 ]. For these reasons, a reduction in radiation doses in LD-RT is an impact of many efforts both clinically and experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…However, an optimal RT regimen is still not clear and under current discussion [ 54 ]. Additionally, due to discussion about a possible carcinogenic late risk, the application of LD-RT is still a subject of controversial debate and less accepted in many countries [ 55 , 56 ]. For these reasons, a reduction in radiation doses in LD-RT is an impact of many efforts both clinically and experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…This vicious relationship which is usually accompanied by GI can be considered without any doubt as the major pathway leading to carcinogenesis [ 144 , 145 ]. Chronic inflammation which is synonymous to the activation of innate immune system can lead to the downregulation of DNA repair pathways and cell cycle checkpoints due to the release of inflammatory mediators and ROS which can lead to GI [ 146 ]. Towards this direction, Colotta et al suggested a few years ago, that cancer-related inflammation can promote GI by the various inflammatory mediators, leading to accumulation of random genetic modification in cancer or healthy cells.…”
Section: Resultsmentioning
confidence: 99%
“…Together, the authors estimate this would result in up to 4000 excess fatal malignancies all together [ 13 ]. Radiation has a stochastic effect meaning that any dose of radiation may lead to the development of malignancy, though higher doses having an increasingly linear dose-effect relationship [ 14 ]. Despite these findings, statistical models do not show evidence that cardiac catheterization leads to the development of malignancy.…”
Section: Discussionmentioning
confidence: 99%